Managing Stock Option Expense: The Manipulation of Option‐Pricing Model Assumptions* - Johnston, Derek (Contemporary Accounting Research, 2006)
Abstract This paper examines whether firms that voluntarily recognize stock option expense in their financial statements manage that expense downward more than firms that do not recognize the expense by adjusting option‐pricing model assumptions. To examine this issue, I collect option‐pricing model assumptions from fiscal year 2002 for both a sample of firms that voluntarily recognize stock option expense (“recognizing firms”) and a sample of control firms that do not (“disclosing firms”). The empirical results suggest that recognizing firms manage the recognized stock‐based compensation expense reported in their financial statements downward more than do firms that only disclose the expense. Additional analyses reveal that recognizing firms assume a lower level of volatility than disclosing firms in the option‐pricing model calculations; however, I find no evidence that recognizing firms manage the dividend yield and risk‐free interest rate assumptions more than disclosing firms. The Financial Accounting Standards Board (FASB) recently issued Statement of Financial Accounting Standards No. 123(R), which requires the expensing of the fair value of stock options, so these results may be of interest to capital‐market participants and the FASB as they assess the reliability of stock option expense as determined by option‐pricing models.